2020
DOI: 10.1111/and.13749
|View full text |Cite
|
Sign up to set email alerts
|

Loranthus micranthusnanoparticles abates streptozotocin‐instigated testicular dysfunction in Wistar rats: Involvement of glucose metabolism enzymes, oxido‐inflammatory stress, steroidogenic enzymes/protein and Nrf2 pathway

Abstract: Therefore, production of plant nanoparticles with known therapeutic potentials is a need of the moment and has prompted the current

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…In recent studies by Griffin et al it was shown that various plant materials can be rendered into nanosized particles by using a combination of high speed stirring (HSS) and high pressure homogenization techniques (HPH) [ 3 , 4 , 5 , 6 , 7 , 8 , 9 ]. Diminution of plant materials to sizes < 10 µm means that all plant cells, which typically possess sizes > 10 µm, are destroyed.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In recent studies by Griffin et al it was shown that various plant materials can be rendered into nanosized particles by using a combination of high speed stirring (HSS) and high pressure homogenization techniques (HPH) [ 3 , 4 , 5 , 6 , 7 , 8 , 9 ]. Diminution of plant materials to sizes < 10 µm means that all plant cells, which typically possess sizes > 10 µm, are destroyed.…”
Section: Introductionmentioning
confidence: 99%
“…The equipment required is low-cost, freely available and meanwhile established in many laboratories world-wide [ 10 , 11 , 12 , 13 , 14 ]. The feasibility of the PlantCrystal technology was proven in previous studies, where PlantCrystals were shown to increase the antimicrobial and antifungal activity of various plant materials [ 3 , 4 , 5 , 6 , 7 , 8 , 9 ]. Their feasibility to improve antioxidative capacity has not yet been investigated and a systematic study investigating the influence of plant material and process parameters on PlantCrystal size and properties is also not yet available.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Melatonin ameliorates ATR-induced mitochondrial dysfunction and steroid disorders in GCs via the ROS/SIRT1/STAR axis ( Li et al, 2024 ). Similarly, Loranthus micranthus nanoparticles can alleviate testicular dysfunction in rats via the steroidogenic enzymes/protein and Nrf2 pathways ( Ebokaiwe et al, 2020 ). However, the specific role of the Nrf2/ARE pathway in regulating ATR-mediated reproductive disorders remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…The destruction of the plant cells and organelles allows for a fast and exhaustive extraction of plant constituents without the need of organic solvents ( Figure 1 ). Thus, the PlantCrystal-technology is considered to be a novel, environmentally friendly plant extraction process; the suitability of the technology over classical extraction methods was already proven in various recent studies [ 1 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 ]. These studies could, for example, show an enhanced extraction efficacy, especially for lipophilic compounds when compared to classical extraction methods and could also demonstrate an improved therapeutic efficacy when compared to classical extracts.…”
Section: Introductionmentioning
confidence: 99%